Accuracy of three-dimensional photogrammetry and cone beam computed tomography based on linear measurements in patients with facial deformities - Zhao, Zhenqi (Dentomaxillofac Radiol, 2021)
OBJECTIVES: This study was aimed to investigate the accuracy of soft-tissue measurements obtained by two imaging modalities, three-dimensional (3D) photogrammetry and cone beam CT (CBCT) when confounded by influence factors (facial deformities and partitions). METHODS: 60 wax facial models from facially deformed patients were captured by 3D photogrammetry and CBCT. 19 linear distances on each image were measured and juxtaposed to reference values attained via a coordinate-measuring machine (CMM) as the gold-standard. Paired t-tests were used to compare linear accuracy of the test and reference systems. The influence of deformities and partitions (created by dividing the face with three vertical and five horizontal lines) on the measurement errors were analyzed by independent sample t-test and one-way ANOVA. RESULTS: Statistically significant differences were found between linear accuracy of the test and reference systems. The test values obtained by 3D photogrammetry were closer to the reference values than CBCT’s. 3D photogrammetry’s measurement errors were significantly higher in deformed areas, unlike CBCT’s. Both systems reported significantly lower errors within partitions 8 and 13 compared to other partitions; for CBCT, aside from partitions 8 and 13, the differences in the errors for partitions 6 and 10 were significant compared to partitions 8, 12, 13, 14. CONCLUSION: 3D photogrammetry showed a higher linear accuracy than CBCT in patients with facial deformities due to protuberances. Facial reconstruction by both test modalities was significantly influenced in different facial partitions, but facial deformities extensively affected the results from 3D photogrammetry.